Knowledge, attitude and practices of asthma food taboos and its associated factors among parents of asthmatic children in Hospital Universiti Sains Malaysia - Ridzuan, Nur Syafiqka Atika Mohd (Universiti Sains Malaysia, 2024)
Asthma food taboos are a set of food prohibitions that may cause asthma attacks. These will impact how well asthma is treated medically. The objectives of this study aim to determine the knowledge, attitude and practice of asthma food taboos and its associated factors among parents of asthmatic children in Hospital Universiti Sains Malaysia. A cross-sectional study design was conducted in this study. Data was collected using a Google Forms. A total of 344 parents with asthmatic children in Hospital USM who fulfilled the inclusion and exclusion criteria were approached to participate in this study. Data collected were statistically analysed using the SPSS software version 27.0. This study showed that 59.9% of respondents have poor knowledge, 67.4% have a positive attitude and 61.3% practice asthma food taboos. There was no correlation between knowledge with attitude (p= 0.663) and knowledge with practice (p=0.683) meanwhile there was a correlation between attitude and practice (p=0.001). Lastly, there was an association between sociodemographic factors [age (p=0.000), and religion (p=0.015)] with the practice of asthma food taboos. Meanwhile, there was no association between sociodemographic factors [ethnicity (p=0.069), and educational level (p=0.831)] with the practice of asthma food taboos among parents with asthmatic children in Hospital USM. It is concluded that parents with asthmatic children have poor knowledge, positive attitudes and high practice of asthma food taboos. Health practitioners must learn more about how culture influences diets and foods that could be harmful or fatal for people with asthma and promote changes in knowledge, attitude, and practice of these asthma food taboos.